2009
DOI: 10.1073/pnas.0908374106
|View full text |Cite
|
Sign up to set email alerts
|

Believers' estimates of God's beliefs are more egocentric than estimates of other people's beliefs

Abstract: People often reason egocentrically about others' beliefs, using their own beliefs as an inductive guide. Correlational, experimental, and neuroimaging evidence suggests that people may be even more egocentric when reasoning about a religious agent's beliefs (e.g., God). In both nationally representative and more local samples, people's own beliefs on important social and ethical issues were consistently correlated more strongly with estimates of God's beliefs than with estimates of other people's beliefs (Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
68
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 22 publications
7
68
1
Order By: Relevance
“…The higher scores on the adjective overlap measure among participants who reported a greater awareness of God could suggest that devoted believers have followed religious teachings that exhort them to be more God-like. Alternatively, they may simply have projected their self-image onto God (Epley et al, 2009). The results for the adjective overlap measures in Study 2 suggest an interesting parallel to the results using these measures from Study 1.…”
Section: Self-god Overlap 347mentioning
confidence: 56%
See 1 more Smart Citation
“…The higher scores on the adjective overlap measure among participants who reported a greater awareness of God could suggest that devoted believers have followed religious teachings that exhort them to be more God-like. Alternatively, they may simply have projected their self-image onto God (Epley et al, 2009). The results for the adjective overlap measures in Study 2 suggest an interesting parallel to the results using these measures from Study 1.…”
Section: Self-god Overlap 347mentioning
confidence: 56%
“…First, as might well be expected, when looking simply at the numbers of adjectives ascribed to God, evangelicals saw both more positive adjectives and fewer negative adjectives as being descriptive of God than did atheists, suggesting that on the balance, evangelicals have a more positive profile for God than atheists do. However, evangelicals do not just see God differently; they see God as being a lot more like themselves (Epley, Converse, Delbosc, Monteleone, & Cacioppo, 2009) and this pattern was evident in the overlapping adjectives that participants endorsed for both God and themselves. Evangelicals saw a much greater percentage of self-descriptive adjectives as also being descriptive of God, an effect largely driven by overlap on positive adjectives.…”
Section: Discussionmentioning
confidence: 76%
“…A provocative series of studies by Epley and colleagues showed that the egocentric tendency to believe that others share one's beliefs is more pronounced when individuals are asked about God than when they are asked about the average American or various prominent individuals (40). The present research is distinct from those studies insofar as its focus is more specifically on such "projection" in the views and also the priorities that liberal and conservative Christians attribute to Jesus Christ.…”
contrasting
confidence: 47%
“…One line of work (Epley, Converse, Delbosc, Monteleone, & Cacioppo, 2009) investigated ideological beliefs, or socially shared beliefs about how the world is and how it should be (e.g., Jost, Federico, & Napier, 2009). Ideologies include beliefs about topics such as abortion and same-sex marriage.…”
Section: Adults' Implicit Representations Of God's Mindmentioning
confidence: 99%